Study on the Relationship between Teacher Leader and Proactive Behavior: Taking Workplace Spirituality and Teacher Grit as Moderator - Ye, YaXi; Zhang, MingShan (วารสารนวัตกรรมการศึกษาและการวิจัย, 2024)
In the post-pandemic era, there is an urgent need to address how to successfully implement educational reforms. And teacher leader and proactive behavior are related to the success of these reforms. Therefore, the relationship between teacher leader and proactive behavior is studied. Two research programs explore the direct and indirect (moderating) roles between teacher leader and proactive behavior, with workplace spirituality and teacher grit used as mediators. The results show that teacher leader has a significant positive effect on proactive behavior, and workplace spirituality and teacher grit have a significant positive moderating effect between teacher leader and proactive behavior. This indicates that only with both perceived inner experience and non-cognitive interest and effort, may teacher leader adequately enhance proactive behavior. Finally, it is suggested that in the educational reform, the focus should be on the development and support of teacher leader and proactive behavior.